Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.14716/ijtech.v8i7.693
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Precursors and Solvents on the Characteristics of Fluorine-doped Tin Oxide Conducting Glass Fabricated by Ultrasonic Spray Pyrolysis

Abstract: Transparent conductive oxide (TCO) glass is one of most important components in dyesensitized solar cell (DSSC) device. In addition to its high electrical conductivity, transparency is another important requirement that must be achieved in fabricating TCO. One TCO film is fluorine-doped tin oxide (FTO), which can be considered as the most promising substitution for indium-doped tin oxide (ITO), since the latter is very expensive. However, the fabrication techniques for TCO film need to be carefully selected; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…So, substrate temperature is more important parameter for preferential orientation in depositing thin film. Moreover, the preferred orientations depend on compounds' source, solvent and growth parameters such as solution and deposition concentration [7,19,20]. The crystallite size (D) of these AFTO thin films is calculated using Debye-Scherrer's formula, D=0.9λ/(βcosθ) [8] where λ is the wavelength (λ=1.5418 Å), β means of the broadening of diffraction line measured at (FWHM) and θ is the Bragg angle.…”
Section: Structural Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…So, substrate temperature is more important parameter for preferential orientation in depositing thin film. Moreover, the preferred orientations depend on compounds' source, solvent and growth parameters such as solution and deposition concentration [7,19,20]. The crystallite size (D) of these AFTO thin films is calculated using Debye-Scherrer's formula, D=0.9λ/(βcosθ) [8] where λ is the wavelength (λ=1.5418 Å), β means of the broadening of diffraction line measured at (FWHM) and θ is the Bragg angle.…”
Section: Structural Analysismentioning
confidence: 99%
“…Transparent on optical range, low resistivity conducting and wide optical band gap (Eg) (>3 eV) oxides (TCOs) have attracted the scientists due to their wide using in many research and industrial areas for example, lowemissivity glass [1], window defrosters [2], transparent anode layer for all general organic light emitting diodes [3] and optoelectronic devices [4][5] gas sensor [6], DSSC solar cell [7] and flat panel TV displays. This combination sort of transparency and conductivity isn't usually possible in intrinsic stoichiometric oxides; however, it is made in a non-stoichiometric composition or with appropriate dopants as Sb, F, Zn, Mo, Pr and Ta [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCOs thin films have deposited with various technique for a long time. It can be given for example spray pyrolysis (Yuwono et al, 2017), spin coating (Kadhim et al, 2017), pulsed laser deposition (Martin et al, 2004), dip coating (Carvalho et al, 2012) and sputtering (Zhu et al, 2017) methods. Among them, it was found that spray pyrolysis method have interesting properties such as simple and inexpensive experimental setup, reproducibility, easily adding of doping materials, preparing thin films with high quality (Tripathi and Shukla, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The properties of TCOs thin films have been fabricated by spray can be changed with substrate temperature, spray time, spray flow rate, nozzle-substrate distance, precursors and solvents etc. (Yuwono et al, 2017). Here, we aimed to compare effect of substrate temperature and molarity on TCOs thin films by spray method (for example SnO 2 :Sb:F).…”
Section: Introductionmentioning
confidence: 99%